Pancreatic Peptides in Young and Elderly Zucker Type 2 Diabetic Fatty Rats - Howarth, Frank Christopher; Al Kitbi, Mey Khalfan Ahmed Ali; Hameed, Rasheed Shaul; Adeghate, Ernest (JOP. Journal of the Pancreas, 2011)
<!–[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> <span style="font-size: 9.0pt; font-family: "Times New Roman"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; layout-grid-mode: line;" lang="EN-US">Context<span style="font-size: 9.0pt; font-family: "Times New Roman"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; layout-grid-mode: line;" lang="EN-US"> The global prevalence of diabetes mellitus, and in particular type 2 diabetes mellitus is increasing at an alarming rate. Risk factors for development of diabetes include obesity and advancing age. Objectives The distribution of insulin, glucagon, somatostatin and pancreatic polypeptide in the pancreatic islets has been investigated in young and elderly type 2 Zucker diabetic fatty (ZDF) rats and age-matched Zucker lean (ZL) controls. Methods Experiments were performed in male animals aged either 9-13 weeks or 30-34 weeks. Immunohistochemistry was used to label insulin, glucagon, somatostatin and pancreatic polypeptide in islet cells. Results The percentage of insulin-positive cells was unaltered in young but decreased in elderly ZDF (35.5±2.5%) rats compared to ZL controls (57.9±1.8%). The percentage of glucagon-positive cells was increased in young ZDF (58.7±3.4%) compared to ZL controls (23.4±2.1%). However, in elderly rats the percentage of glucagon-positive cells declined in ZDF rats and was no longer different from ZL controls. The percentage of somatostatin-positive cells was unaltered in young and elderly ZDF rats compared to ZL controls. The percentage of pancreatic polypeptide-positive cells was unaltered in young but increased in elderly ZDF (22.0±2.5%) rats compared to ZL controls (13.8±1.8%). Conclusions The distribution of pancreatic hormones is altered to varying extents in the ZDF rat and during the normal aging process.